Analisis Penerapan SOP Pelayanan E-KTP Pada Disdukcapil Kota Tanjung Pinang - Ramadiyati Okta Putri; Aslamaturrahmah Dwi Putri; Nazaki Nazaki (CV. ITTC INDONESIA, 2026)
This study was prepared to examine the implementation of Standard Operating Procedures (SOP) in E-KTP services at the TanjungPinang City Population and Civil Registration Office, recognize obstacles that arise during its implementation, and identify the actions taken to improve the quality of service. The method used in this study is qualitative descriptive with data collection techniques through observation and interviews. The findings of this study indicate that the implementation of the SOP for E-KTP services has been carried out in accordance with existing provisions, starting from document acceptance, data validation, data recording, to printing E-KTP. However, in the acting, several obstacles are still found, including a fairly long service queue, disruptions to the Population Administration Information System (SIAK), and low public understanding of service procedures and requirements. Efforts that can be made to improve service quality include increasing network stability, expanding the distribution of information to the community, and conducting regular service evaluations. With these steps, it is hoped that the E-KTP service at the Tanjungpinang City Disdukcapil can operate more efficiently and effectively.